The philosophy of money - Simmel, Georg (Routledge, 2013)
In The Philosophy of Money, Georg Simmel puts money on the couch. He provides us with a classic analysis of the social, psychological and philosophical aspects of the money economy, full of brilliant insights into the forms that social relationships take. He analyzes the relationships of money to exchange, human personality, the position of women, and individual freedom. Simmel also offers us prophetic insights into the consequences of the modern money economy and the division of labour, in particular the processes of alienation and reification in work and urban life.